Wula (Voices) of Aboriginal women on barriers to accepting smoking cessation support during pregnancy: Findings from a qualitative study. Issue 1 (February 2018) - Bovill, M.; Gruppetta, M.; Cadet-James, Y.; Clarke, M.; Bonevski, B.; Gould, G.S.
Abstract: Aim: To gather Aboriginal women's stories of smoking and becoming pregnant to identify the barriers in accepting smoking cessation support during pregnancy. Methods: Qualitative data were collected through use of yarning methodology between August 2015 and January 2016 by an Aboriginal Researcher with experience in social and community services. A short on-line survey was used to collect quantitative data. Interviews only recorded the therapeutic yarning process, which ranged from 9 to 45 min duration, averaging 30 min. Audio-recorded interviews were transcribed and independently coded. A general inductive analysis was used to determine emergent themes. Results: Twenty Aboriginal women between 17–38 years of age, who were pregnant or recently given birth, living in the Hunter New England (HNE) area took part. Eleven women were still smoking; nine had quit. Most were highly aware of the implications of smoking for their babies. Major themes identified for accepting support were: ambivalence towards a need for support, health professional advice, reduction in smoking, and attitudes to Nicotine Replacement Therapy (NRT). Women reported being advised to cut down, rather than to quit; reducing consumption may be a barrier to accepting NRT. Women recommended enhanced clinical support and Aboriginal community engagement in cessation care. Discussion/conclusions: Aboriginal women in the HNE area reported quitting or reducing their cigarette intake during pregnancy. Health Professionals working with Aboriginal women during pregnancy should give consistent messages to quit smoking completely, and offer increased, ongoing and extensive smoking cessation support to Aboriginal mothers. Clinical practices could partner with Aboriginal communities to support the delivery of smoking cessation services.